The barriers of normalizing development for residential green buildings in Perak Tengah region / Muhammad Farid Reza and An Nisha Nur Welliana Abd Rased - Reza, Muhammad Farid; Abd Rased, An Nisha Nur Welliana (2023)
This paper examines the potential barriers of normalizing development for residential green buildings. The details and effects of green buildings are stated and as well as their impacts to the economy and surrounding environment. By integrating green design concepts into residential developments, the aim is to promote a greener and cleaner environment. These buildings are constructed with the goal of minimizing resource usage and ensuring long-term sustainability. To gather insights on the subject, semi structured interviews were conducted with five registered contractors around the Perak Tengah region. Their perspectives provide valuable insights into the topic at hand by listing out the barriers and generate recommendations in order to solve the issues. The study provides insight on why green residential developments are not in the norm of housing projects. The barriers are then ranked based on data collected to determine the common factors in the study. These findings may assist local governments, housing developers and construction industries on overcoming the barriers of developing green residential housing.